IMPROVED MANUFACTURING CANNED "COMPOTE CHERRY" USING COMBINED HEAT TREATMENT - A. F. Demirova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The results of studies on the development of new modes of heat sterilization compote cherry using stepwise heating in a stream of hot air and hot water dushevaniem air cooled rotating container. Revealed that the modes provide commercial sterility of finished products, reducing the length of the heat treatment and the quality of the finished product. Are some of the modes of heat sterilization step of cherry compote in a stream of heated air and water dushevaniem air-cooled rotating container.